Rbbp4 loss disrupts neural progenitor cell cycle regulation independent of Rb and leads to Tp53 acetylation and apoptosis. Issue 8 (18th March 2022) - Schultz‐Rogers, Laura E.; Thayer, Michelle L.; Kambakam, Sekhar; Wierson, Wesley A.; Helmer, Jordan A.; Wishman, Mark D.; Wall, Kristen A.; Greig, Jessica L.; Forsman, Jaimie L.; Puchhalapalli, Kavya; Nair, Siddharth; Weiss, Trevor J.; et al.
Abstract: Background: Retinoblastoma binding protein 4 (Rbbp4) is a component of transcription regulatory complexes that control cell cycle gene expression. Previous work indicated that Rbbp4 cooperates with the Rb tumor suppressor to block cell cycle entry. Here, we use genetic analysis to examine the interactions of Rbbp4, Rb, and Tp53 in zebrafish neural progenitor cell cycle regulation and survival. Results: Rbbp4 is upregulated across the spectrum of human embryonal and glial brain cancers. Transgenic rescue of rbbp4 mutant embryos shows Rbbp4 is essential for zebrafish neurogenesis. Rbbp4 loss leads to apoptosis and γ‐H2AX in the developing brain that is suppressed by tp53 knockdown or maternal zygotic deletion. Mutant retinal neural precursors accumulate in M phase and fail to initiate G0 gene expression. rbbp4 ; rb1 mutants show an additive effect on the number of M phase cells. In rbbp4 mutants, Tp53 acetylation is detected; however, Rbbp4 overexpression did not rescue DNA damage‐induced apoptosis. Conclusion: Rbbp4 is necessary for neural progenitor cell cycle progression and initiation of G0 independent of Rb. Tp53‐dependent apoptosis in the absence of Rbpb4 correlates with Tp53 acetylation. Together these results suggest that Rbbp4 is required for cell cycle exit and contributes to neural progenitor survival through the regulation of Tp53 acetylation. Key Findings: Rbbp4 regulates neural progenitor cell cycle independent of Rb Rbbp4 loss leads to Tp53 acetylation, gamma‐H2AX labeling and apoptosis in neural progenitors Suppression of gamma‐H2AX labeling and apoptosis by Tp53 knockdown in Rbbp4 mutants indicates Rbpp4 may induce apoptosis by transcriptional activation of Tp53 independent of the DNA damage response pathway